PENGARUH TINGKAT PENDIDIKAN, TINGKAT PENGETAHUAN, KUALITAS SUMBER DAYA MANUSIA, PEMAHAMAN AKUNTANSI, DAN PEMANFAATAN TEKNOLOGI TERHADAP PENGGUNAAN SISTEM INFORMASI AKUNTANSI PADA UMKM - Trimarlani, Chika (TEMA, 2023)
This study aims to determine the effect of education level, knowledge level, quality of human resources, understanding of accounting, and use of technology on the use of accounting information systems in SMEs in Pati Regency. The independent variables tested in this study were the level of education, level of knowledge, quality of human resources, understanding of accounting and use of technology, while the use of accounting information systems was the dependent variable. The sample of this research is MSME owners who have used technology and implemented systems in their businesses such as owners of basic food/grocery shops, cellphone counters, and several other MSMEs. The sample selection was carried out using the convenience sampling method. The data used is primary data, obtained from a questionnaire with a total of 125 respondents. The data obtained were then tested using Multiple Regression Analysis at a significance level of 5% using the SPSS 22 system. The test results identified that the level of Education, Level of Knowledge, Quality of Human Resources, Understanding of Accounting, and Utilization of Technology had a positive and significant effect on the use of information systems accounting for SMEs in Pati Regency.